Influence of grinding on the roundness, residual stresses and microstructure of VC131 steel analysed by varying the type of cutting fluid - Catai, Rodrigo Eduardo; Bianchi, Eduardo Carlos [UNESP]; de Sampaio Alves, Manoel Cléber [UNESP]; de Aguiar, Paulo Roberto [UNESP] (My University, 2008)
This paper by R. E. Catai, E. C. Bianchi, P. R de Águia and M. C. Alves reports on the results of an analysis made of roundness errors, residual stresses, and SEM micrographs of VC131 steel. The analysis involved workpieces ground with two types of cutting fluid: synthetic cutting fluid and emulsive oil. In this study, the cutting parameters were kept constant while the type of cutting fluid was varied. The amount of cutting fluid injected in the process was also varied, aiming to identify the ideal amount required to obtain good results without causing structural damage to the workpiece. The SEM analyses of roundness errors and residual stresses revealed that, of the two cutting fluids, emulsive oil provided better tensions due to its greater lubricating power.
Keywords: Error analysis; Errors; Fluids; Iron; Lithography; Residual stresses; Secondary emission; Steel; Steel analysis; Strength of materials; (e ,3e) process; cutting parameters; SEM micrographs; Structural damages; Two types; Work-piece (WP); Work-pieces; Cutting fluids